Influencia Del Comité De Auditoría En El Desempeño Financiero Organizacional, En Empresas Mexicanas Cotizadas (2010-2014) - Jiménez, Sergio Demetrio Polo; González, Eleazar Villegas; Alvarado, Martha Jiménez; Benítez, C. Daniela Martín (European Scientific Journal, ESJ, 2018)
The purpose of this paper is to know the level of compliance with corporate practices related to the audit function, contained in the Code of Best Corporate Practices, issued by the National Banking and Securities Commission and influence on organizational financial performance (specifically on financial profitability), for this, a sample of 405 questionnaires of best corporate practices, belonging to 125 non-financial companies, are listed on the Mexican Stock Exchange during the period, 2010-2014. The results of the application of the linear regression model, could allow us to affirm that the Audit Function (INDEX_FA), increases the financial profitability of the organizations, which is a great success on the part of the Mexican regulators.